ANALYZING THE NATURALNESS AND ACCURACY OF STUDENT'S TRANSLATION OF CHILDRENT'S STORIES - Astri Yuniar Sri Utari, - (2008)
This research tried to analyze the naturalness and accuracy of students' translation in translating three children stories; Little Lily at Flower land, Little Lily at Candy land, and The sky is falling! by examining the aspects of naturalness and accuracy based on Newmark (1988). They are word order, common structures, cognate words, lexical words, colloquial words, and onomatopoeic words. Those aspects were investigated through the methods that used by the students. This research used qualitative approach. The result suggested that the students' translations were natural and accurate, since most of them could achieve the aspects of naturalness and accuracy. The writer found seven translation methods applied in the translations; communicative, word-for-word, free, idiomatic, semantic, faithful, and literal translation method. The most frequently used by students were communicative, word-for-word, and free translation. The problems that mostly occur in their translations were the matter of diction and grammatical structures.